Propuesta diseño en planta para las nuevas instalaciones de la empresa Casa Muebles Rivera en el Valle del Cauca (2022)
The present degree work it took place in a company that manufactures mattresses, belonging to the secondary economic. In this project, the propositive methodology and qualitative and explanatory research were applied Where it was made the diagnosis of the current situation of the plant, using engineering tools and methodologies for data collection and analysis, some of them were: flowcharts, planimetry, route diagram, whit the purpose to obtain information and document how the mattress production process is. This investigation has as main objective make a plant layout, in a new headquarters that the company acquired in another geographical location